Charcot’s osteoarthropathy – Lest we forget (Indian Journal of Case Reports, 2024)
Charcot’ osteoarthropathy (COA) is a rare, often misdiagnosed inflammatory debilitating complication of conditions most common being diabetes that needs to be discussed further to prevent associated morbidity. The natural history of the disease sees four stages and requires prompt diagnosis and treatment to ensure the desired outcome. We describe a case series of two cases of diabetes-associated osteoarthropathy and their management. A 72-year-old male with the early COA was managed with a total contact cast for both lower limbs and an 80-year-old male with the early COA with bone marrow edema in the tibia and talus, as well as, subtalar effusion, managed conservatively. The follow-up review documented clinical recovery in the form of a marked reduction in swelling of the lower limbs with the resolution of the functional status of lower limbs. It is the responsibility of every physician to ensure the goals of management which includes immediate offloading and good glycemic control.